Utilización de variables citogenéticas y antropométricas para un eficiente manejo de primates neotropicales en cautiverio - Ferre, D. (2009)
The neotropical primates which are part of the collection of the Mendoza Zoological Garden (ZMA) were object of a collaborative study that included the performance of anthropometrical measurements and classic cytogenetic analysis (alpha). Thirteen specimens of the genus Alouatta (10 females and 3 males), 2 Cebus sp. (1 male and 1 female) and 3 females of Saimiri sp. were studied. The karyological study allowed to confirm that the Cebus of ZMA corresponded to Cebus paraguayanus (2N=54, XX/XY) and the Saimiri to Saimiri boliviensis boliviensis species (2N = 44, XX). In the howler monkeys the species assignment was confirmed to A. caraya and a chromosomal morphology in the mitotic metaphases, compatible with the previously described and confirmed by meiosis, multiple sex determination system X1X1X2X2/X1X2Y1Y2, was observed. This opportunity allowed the ZMA to implementthe identification through the injection of numerated microchips that will facilitate its following and management.